Design of multi-layered architecture in dissimilar ceramic/metal joints with reinforcements clustering away from both substrates. (15th January 2021) - Feng, Qinghua; Lin, Panpan; Ma, Guanglu; Lin, Tiesong; He, Peng; Long, Weimin; Zhang, Qiuguang
Abstract: To combine the advantages of ductile fillers and composite fillers and alleviate residual stress in joints between ZrB2 -SiC ceramics (ZS) and TC4-TiBw composites, a novel multi-layered joint architecture composed of a layer of clustering SiC at the center of the joint (L-C-SiC) and two ductile layers without SiC particles bordering both substrates (L-DS) was designed. To achieve this, SiC particle skeletons with continuous micro-channels (SSCC) were integrated with AgCu filler as an interlayer. The effects of SSCC porosity and brazing temperature on joint microstructure and mechanical properties were investigated. In particular, the braze/ZS and braze/SSCC interfaces were analyzed through X-ray diffractometry (XRD), transmission electron microscopy (TEM), and wavelength-dispersive spectroscopy (WDS). The residual stress was also evaluated. The results indicate that increasing the brazing temperate improved the infiltration into the SSCC and promoted the SSCC/braze interface reaction (was detrimental to the SiC particle skeleton). Reducing the SSCC porosity changed the thicknesses of the two L-DSs and enhanced the inhomogeneity of the SSCC/braze interface reaction (induced a shear stress in L-C-SiC). For brazing with an interlayer of 30% porosity at 820 °C, the joint shear strength reached a maximum of ~41.2 MPa, mainly due to the construction of the multi-layered joint architecture. Graphical abstract: Unlabelled Image Highlights: SiC particles clustered away from both substrates in joint. Ductile layers without SiC particles bordered on both substrates. Multi-layered joint architecture was achieved. Multi-layered architecture mitigated residual stress in joints. This design combined advantages of ductile fillers and composite fillers.